2018
DOI: 10.1038/nrn.2017.170
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria at the neuronal presynapse in health and disease

Abstract: Synapses enable neurons to communicate with each other and are therefore a prerequisite for normal brain function. Presynaptically, this communication requires energy and generates large fluctuations in calcium concentrations. Mitochondria are optimized for supplying energy and buffering calcium, and they are actively recruited to presynapses. However, not all presynapses contain mitochondria; thus, how might synapses with and without mitochondria differ? Mitochondria are also increasingly recognized to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
386
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(391 citation statements)
references
References 228 publications
(268 reference statements)
3
386
0
2
Order By: Relevance
“…; Smith et al . ; Devine & Kittler, ). Pharmacological approaches have shown that mitochondria can regulate short‐term plasticity by adjusting Ca 2+ ‐dependent neurotransmitter release and synaptic vesicle recycling, and act to fulfil bioenergetic demands of the synapse by maintaining ATP during intense synaptic activity (Alnaes & Rahamimoff, ; Tang & Zucker, ; Li et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Smith et al . ; Devine & Kittler, ). Pharmacological approaches have shown that mitochondria can regulate short‐term plasticity by adjusting Ca 2+ ‐dependent neurotransmitter release and synaptic vesicle recycling, and act to fulfil bioenergetic demands of the synapse by maintaining ATP during intense synaptic activity (Alnaes & Rahamimoff, ; Tang & Zucker, ; Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…The ability of a synapse to successfully stimulate its postsynaptic accomplice depends on many presynaptic factors: calcium concentration, efficacy of fusion proteins for exocytosis, number of vesicles primed for release, and availability of cellular energy to fuel these processes. Using the calyx of Held as a model for examining presynaptic function, we hope to contribute to a greater mechanistic understanding of the synaptic basis of neurological and neurodegenerative diseases where dysregulation of mitochondrial dynamics and function is a likely culprit (Devine & Kittler, ). Here, we show DRP1 loss from the presynaptic compartment results in altered mitochondrial morphology and severe defects in multiple facets of synapse physiology.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Particularly, these cells secret proinflammatory cytokines called senescence-associated secretory phenotype (SASP), which can accelerate the cells' further senescence (autocrine effect) or induce other cells' senescence (paracrine effect). 61,62 Kwon et al 63 demonstrated that mitochondria regulated presynaptic calcium homeostasis and thus in turn controlled neurotransmitter release. 59,60 Mitochondria can affect synapse activities and instigate abnormal transportation of neurotransmitters.…”
Section: Mitochondria In Depressionmentioning
confidence: 99%
“…Pre‐synaptic mitochondrial abundance can be fine‐tuned owing to dynamic anterograde/retrograde trafficking. As Devine and Kittler review some neurons are devoid of pre‐synaptic mitochondria. Perhaps their absence masks synapse pruning, provided mitochondria can quickly re‐populate synapses to support neuronal activity .…”
Section: Potential Strategies For Regulating Mitochondrial O2−/h2o2mentioning
confidence: 99%